Synthesis, Characterization, and Cytotoxicity Research of Sulfur-Containing Metal Complexes - Yanting Yang; Danqin Li; Mei Luo (Inorganics)
In this experiment, the excellent coordination ability of sulfur-containing ligands was utilized. Diphenylacetyl disulfide and 3,3′-diaminodiphenyl sulfone were selected as ligands, and Cu(NO3)2·3H2O, Ni(NO3)2·6H2O and ZnCl2 were reacted under one-pot conditions to synthesize three mononuclear complexes: [C4H18CuO12S2](I), [C12H18N4NiO11S](II) and [C24H24Cl2N4O4S2Zn](III). Complex (I) belongs to the orthorhombic crystal system with space group Pbca, while complexes (II) and (III) belong to the monoclinic crystal system with space groups P21/n and P2/n. The crystal structure of the complex was determined using X-ray diffraction (XRD). The structure of the complex was analyzed using infrared Fourier transform infrared spectroscopy (FT-IR), ultraviolet–visible spectroscopy (UV–Vis), nuclear magnetic resonance (NMR), and electrospray mass spectrometry (ESI-MS), and the thermal stability and composition of the complex were detected via thermogravimetry (TGA). In terms of application, the biological activity of complexes (I)–(III) in human cancer cell lines (lung cancer A549, liver cancer SMMC-7721, breast cancer MDA-MB-231, and colon cancer SW480) was tested using the MTS method. The results showed that complex (II) had a good inhibitory effect on breast cancer MDA-MB-231.